The Mortgage Guarantee as the Settlement Effort of Non-Performing Loan and the Resistance In the Execution of Collateral - Monica Windiar; Rahmi Zubaedah; Rani Apriani (Unram Law Review, 2021)
This article aims is to acknowledge the factors of a Non-Performing Loan. Also, to acknowledge on how to settle the non-performing loan with the mortgage guarantee through the litigation or non-litigation way, as well as the obstacle on mortgage guarantee execution by the creditor (Bank). The method of this research using a normative (library) research which is the research on the secondary data. The problem approach of this research is normative juridic, the specification of this research using analysis descriptive, in the field research the writer using 3 (three) methods which is done through an interview, questionary lists and document. The location of this research is PT. Bank Danamon branch of Purakarta. The result of this research shows that the factors which causes of a Non-Performing Loan by the debtor from the internal and external factors. The internal factors are a situation where the debtor unable to pay his loan that have matured because of the burden of the installment is too heavy, the debtor who is on purpose to not fulfill the installment and from the creditor party or bank because of the calculation mistake even though this matter is very rare to be occurred. Hence, the external factor is a factors outside the creditor and debtor capability which causes by the Force majeur, the settlement effort of non-performing loan with the mortgage guarantee may be divided into two parts which are: Litigation and Non-Litigation ways, the obstacle on the mortgage execution by the reciprocal or lawsuit to the court which is done by the third party at the time of the auction sale will be performed.